Molecular modeling studies of c-terminal arginine repressor protein (ARGRC) interaction with its co-repressor, L-arginine - Merican, Amir Feisal; Rahman, N.A.; Asi, A.M. (Malaysian Society for Molecular Biology and Biotechnology, 2000)
In Escherichia coli, the arginine repressor protein C-terminal domain of ArgR (ArgRc) regulates the transcription of L-arginine biosynthetic genes and is involved in Xer site-specific recombination. ArgR requires L-arginine, its co-repressor, for DNA binding and hexamerization. X-ray crystallographic data of the hexameric ArgRc in the presence of L-arginine has been reported by Van Duyne ct al. in 1996. This paper presents the results from the molecular modeling studies of the ArgRc-L-arginine interactions. Hydrogen atoms were added to the molecular data of ArgRc protein obtained from the Brookhaven Protein Databank at 2.2 angstrom (A) resolution. The molecule was minimized using the Discover module of the MSI Insight II software to ensure that all the hydrogen atoms are in the appropriate position. The computer model has revealed additional information on the protein-ligand interaction not mentioned in the published X-ray analysis. Amongst the interesting information obtained are models of the interactions between mio L-arginine molecules interfacing in a "circular fashion" within four subunits of ArgRc. It was also observed that the L-arginine-ArgRc interactions extends from the centre of the hexamer to the surface area that are joined to the hinge region of the N-terminal domain.